Learning management based on character education in education subjects through online learning - Faizah, Nurul; 'Alam, Ghasa Faraasyatul; Şaban, Ömer (Priviet Social Sciences Journal, 2026)
This study aims to discover and analyze the implementation of character education-based learning management in online learning during the COVID-19 pandemic, including Educator Professional Ethics and Introduction to Education, through compulsory education courses. This study used a qualitative approach and descriptive types. Observations, field records, documentation, and articles were used as the data sources. The Miles and Huberman Models are used in data analysis procedures, with stages of data collection, data display, data reduction, and data verification. According to the findings, character education was conducted during online learning through cooperation between students and lecturers. Lecture rules, such as face-to-face meetings, can still be followed by students and lecturers. Students and lecturers cooperate to implement ethical principles in discussion forums, such as asking questions and responding to responses.